The effects of temperature-elevation gradients on snowmelt in a high-elevation watershed - Sears, Megan G., author; Fassnacht, Steven, advisor; Kampf, Stephanie, committee member; Rasmussen, Kristen, committee member (Colorado State University. Libraries, 2022)
The majority of snowmelt in the western U.S. occurs at high elevation where hydrometeorological measurements needed for monitoring snowpack processes are often in complex terrain. Data are often extrapolated based on point measurements at lower elevation stations and the elevation to be modeled. In this study, we compute near-surface air temperature-elevation gradients and dew point temperature-elevation gradients (TEG and DTEG, respectively) and compare values to widely accepted rates (e.g., environmental lapse rate). Further, the implications on snowmelt modeling of TEG and DTEG versus accepted temperature-elevation gradients are quantified using two index snowmelt models, 1) temperature and 2) temperature and radiation. TEG and DTEG were found to be highly variable and during nighttime often influenced by cold air drainage. Several modeling scenarios were applied that manipulated air temperature and dew point temperature, via incoming longwave radiation. When compared to the control scenario, these scenarios ranged in snow-all-gone date by -1 to +6 days. The model utilizing observed air temperature and an estimated DTEG performed most similarly to the control scenario. Thus, the estimated DTEG is adequate for index snowmelt models used in similar domains; however, further investigation should be done prior to applying the environmental lapse rate or other estimated TEG values.